(untitled) (Global Journal of Science Frontier Research, 2018)
We find new exact models for the Einstein-Maxwell equations using the polytropic equation of state. The models generated satisfy uncharged star with anisotropy present. It is interesting that our anisotropic polytropic models contain isotropic case at the vanishing point of anisotropic parameters. In all models, the matter variables and gravitational potentials are well behaved. The radial and tangential pressures are compared at different values of polytropic index .